Analysis of energy efficiency of a superconducting short circuit current limiter - Dan’ko, Vladimir; Goncharov, Eugene; Polyakov, Igor (Eastern-European Journal of Enterprise Technologies, 2016)
The work deals with theoretical and experimental studies, aimed at increasing operational indicators of high-temperature superconducting short circuit current limiter of inductive type. We designed a high-temperature superconducting current limiter of inductive type with a superconductive screen, a superconductive winding and a core, which are placed in a general cryostat, which ensures an improvement in energy efficiency. The inductances of magnetic system of a current limiter were determined for the nominal and emergency operating modes. A special feature of the proposed procedure for the calculation of power losses in a current limiter, as well as the magnitude of heat flows to a cryostat, is the fact that the developed procedure considers design parameters of magnetic system with complete cryogenic cooling. Based on the developed procedure, we carried out analysis of the power losses of a superconducting current limiter of inductive type and heat tides to the cryostat for the nominal regime, which demonstrated that the effect of cryogenic cooling of magnetic circuit on the power of heat release of a current limiter is insignificant and amounts to less than one percent. We simulated the work of experimental model of the magnetic system of a current limiter of inductive type during cryogenic cooling with liquid nitrogen. The calculation procedure proposed makes it possible to analyze energy efficiency while determining necessary critical parameters of a superconducting current limiter. It was experimentally explored that the power losses under the nominal mode in the magnetic circuit of a superconductive current limiter of inductive type are insignificant, which corresponds to the previous theoretical calculations. The conducted experimental research confirmed theoretical positions and developed mathematical models.